Effect of Compensation, Work Discipline and Work Culture on Employee Satisfaction of PT. Antarmitra Sembada - Heri Iswanto (Peneliti.net, 2022)
This research aims to find out the influence of compensation, work discipline and work culture on job satisfaction of PT Antarmitra Sembada employees. Analytical technique uses statistical analysis with multiple linear regression testing, determination and hypothesis testing. Compensation research results have no effect on employee job satisfaction by 0 %. Work discipline simultaneously has a significant effect on employee job satisfaction and has an influence contribution of 6.3. Work culture has a significant effect on employee job satisfaction with a contribution of 7.9 %, it is proven that compensation, work discipline and work culture simultaneously have a positive and significant effect on job satisfaction of PT Antarmitra Sembada employees by 10.4%.